Some Investigations on the Anisotropy of the Chemical Etching of (h k 0) and (h h l) Silicon Plates in a NaOH 35% Solution. Part II: 3D Etching Shapes, Analysis and Comparison with KOH 56% - C. R. Tellier; C. A. Hodebourg; S. Durand (Active and Passive Electronic Components)
This paper deals with the micromachining of various (h k 0) and (h h l) membrane–mesa structures in a NaOH 35% solution. Final etching shapes of micromachined structures show a marked anisotropy of type 1. Etching shapes are analysed in terms of the kinematic and tensorial model for the anisotropic dissolution of crystals. Some of crystallographic planes limiting membranes and mesa are identified from a stereographic analysis of top contours. Conclusions of this study are in close agreement with a previous work.